2011
DOI: 10.4414/smw.2011.13206
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute myocardial infarction after implementation of a public smoking ban in Graubünden, Switzerland: Two year follow-up

Abstract: Compared with the two years preceding the implementation of a smoking ban, the incidence of AMI remained significantly reduced in the second year of the ban in Graubünden, whereas no similar reduction was seen in a comparable area without smoke-free legislation. Changes in outdoor air pollution or the use of lipid-lowering drugs did not substantially contribute to the decrease in the incidence of AMI that occurred after adoption of the ban in Graubünden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
(21 reference statements)
0
22
0
2
Order By: Relevance
“…For studies that provide multiple estimates of the change in hospitalization rates for different time periods after law implementation, 15, 17, 23, 28, 38, 42 we used the estimate from the longest follow-up period to prevent double-counting in the meta-analysis. Separately, we performed a metaregression to test whether hospitalization rates changed over time following implementation of the law; in this case, we included all available estimates from various time points.…”
Section: Methodsmentioning
confidence: 99%
“…For studies that provide multiple estimates of the change in hospitalization rates for different time periods after law implementation, 15, 17, 23, 28, 38, 42 we used the estimate from the longest follow-up period to prevent double-counting in the meta-analysis. Separately, we performed a metaregression to test whether hospitalization rates changed over time following implementation of the law; in this case, we included all available estimates from various time points.…”
Section: Methodsmentioning
confidence: 99%
“…Of 1,672 studies identified, 31 studies 22, 2629, 3743, 6177 met the inclusion criteria and were included in this review (Supplementary Figure 1). The article from McAlister et al 78 included in the most recently published systematic review 12 was excluded, as it did not meet our eligibility criteria (this study estimated the effects of tobacco control activities, especially smoking cessation programs, but did not include a smoking ban in public places).…”
Section: Resultsmentioning
confidence: 99%
“…17, 18 When several papers had been published on the same population 19–30 , we selected the publication with the longest follow-up period or the most recent publication (if follow-up periods were equivalent). 19, 2629 Several studies reported the impact of city smoking legislation 21, 23, 31–36 and were later followed by publications reporting state-wide (for US studies) or national legislation. 22, 37, 38 Due to the potential for overlap in study populations, we excluded studies that reported the impact of city legislations and reported data from state/country-wide studies.…”
Section: Methodsmentioning
confidence: 99%
“…Après application des critères d'inclusion et d'exclusion mentionnés dans la méthodo-logie, 17 articles sur l'association entre la pollution particulaire et l'IDM et/ou l'AVC ont été analysés (Tableau 1). [11], la qualité de l'air relativement bonne dans leurs aires d'études respectives (Tableau 2) pourrait expliquer l'absence de signification statistique de l'association entre PM10 et maladie cardiovasculaire. De ce fait, la pollution de l'air ne serait pas un facteur majeur de risque notamment d'IDM dans ces régions comparées à celles qui présentent des niveaux de pollution atmosphérique élevés.…”
Section: Résultatsunclassified